Evaluation and Management of Herniated Lumbar Disc - Roghani, Inayat Shah; Ali, Mumtaz (Journal of Postgraduate Medical Institute, 2011)
Headache and backache are both common symptoms known to human being since the beginning of recorded history. Backache has been part of human experience. About 80% of general adult population will suffer from back pain at some point in their lives and about 35% will develop sciatica. The proportion is very small in children.